Exploring exhaled breath biomarkers for lactose intolerance diagnosis: the Lactobreath pilot study protocol - Daniel Pohl; Stamatios Giannoukos; Kathryn Jane Burton-Pimentel; Roxane Guillod; Guy Vergères (BMJ Open)
Introduction Food intolerances are prevalent in Europe and can cause considerable physical discomfort, dietary restrictions and psychosocial challenges. Among the prominent causes of food intolerance are defects in the digestion and/or transport of short-chain fermentable carbohydrates, fermentable oligo-, di-, monosaccharides and polyols (FODMAPs). A common diagnostic tool for food intolerance is the hydrogen breath test, which monitors the production of H2 gas from the fermentation of ingested FODMAPs by colonic microbiota. However, this method is limited due to its relatively poor correlation with gastrointestinal (GI) symptoms experienced by patients. Diagnosis is complicated as food intolerance is often associated with functional GI disorders, while FODMAPs may exert their effects individually or in combination. Further research on the pathophysiology and the impact of intervention strategies for these conditions is required to improve the diagnosis of food intolerance.Methods and analyses The Lactobreath pilot study is a randomised, two-arm, double-blinded controlled study. 120 healthy, free-living adults will undergo 6-hour postprandial tests with lactose or glucose (control) to investigate the molecular composition of human exhaled breath (exhalome) as a potential source of biomarkers associated with clinical and metabolic traits of lactose malabsorption (Lactobreath profiles). This serves as a proof-of-concept for the future application of this technology in diagnosing food intolerance. We will use a sensitive, non-invasive, real-time measurement technique based on secondary electrospray ionisation coupled with high-resolution mass spectrometry to analyse the chemical profile of the postprandial exhalome after lactose ingestion. Symptoms of lactose intolerance will be assessed using a standardised questionnaire and mechanistically linked to specific key metabolites of the discriminating breath profile. In parallel, a solid-state sensor will measure postprandial hydrogen gas in breath samples, while GI gases (CH4, H2, O2) and intestinal transit time will be monitored using a novel ingestible gas sensor (Atmo Gas capsule). Metabolites in urine, including lactose-derived metabolites, will be investigated using gas chromatography coupled with mass spectrometry. Postprandial bowel sounds will be recorded by wearable sensors (DigeHealth AG). Baseline assessments will be completed before the dietary challenge to capture usual dietary intake (repeated 24-hour recall), faecal microbiota (shallow shotgun sequencing) and to evaluate genetic polymorphisms using saliva samples (PCR analysis of selected penetrant single-nucleotide polymorphisms).Ethics and dissemination The Lactobreath study has been approved by the Ethics Committee of the Canton of Zurich, Switzerland (#2023-01639). The project results will be published in open-access journals, presented at national and international conferences and communicated to the public and other relevant stakeholders via the communication channels of all investigators and partners. All results derived from the study will be accessible, in line with the Swiss National Science Foundation open access policy.Trial registration number NCT06177938.